Efficient synthesis of EDOT modified ABBB-type unsymmetrical zinc phthalocyanine: optoelectrochromic and glucose sensing properties of its copolymerized film - Goktug, Ozge; Soganci, Tugba; Ak, Metin; Sener, M. Kasim (ROYAL SOC CHEMISTRY, 2017)
A new unsymmetrical zinc(II) phthalocyanine (ZnPc2) bearing one EDOT group was efficiently synthesized as a monomer through the statistical condensation reaction. The other products of mixed cyclotetramerization ZnPc1, ZnPc3 and ZnPc4 were also isolated. Obtained ZnPc2 is a good precursor for the synthesis of new functional linear electropolymers. This was approved by the successful electrochemical copolymerization reaction between ZnPc2 and SNS type monomer HKCN in which the amino group was desired for the enzyme immobilization. The electrochromic and glucose sensing properties of copolymer P(ZnPc2-co-HKCN) obtained by electrochemical oxidative polymerization were investigated. Based on spectroelectrochemical studies, the P(ZnPc2-co-HKCN) copolymer showed a greenish yellow colour in the reduced state and a dark blue colour in the oxidized state as a film. An optical contrast ratio of 44% at 471 nm was achieved with a fast switching time (2.5 s). Meanwhile, the novel biosensor constructed from P(ZnPc2-co-HKCN) showed a linear amperometric response to glucose within a concentration range of 0.1 mM to 1.5 mM (LOD: 0.049 mM). These data illustrate the possible use of the P(ZnPc2-co-HKCN) modified electrode as an amperometric glucose sensor.
Keywords: CONDUCTING POLYMERS; SUBSTITUTED PHTHALOCYANINES; SILICON PHTHALOCYANINES; PERIPHERAL POSITIONS; HYDROGEN-PEROXIDE; ELECTROPOLYMERIZATION; DERIVATIVES; METALLOPHTHALOCYANINES; ELECTROCHEMISTRY; ELECTROCHROMISM; Chemistry